The Influence of Change in Costs, Market Age, Capacity Utilization, Supply Chain Management on Bank’s Competitive Advantage - Nadiah, Nadiah; Rosyidi, Suherman (International Journal of Supply Chain Management, 2020)
The goal associated with the current article is to examine the impact of change in cost along with market age, capacity utilization and supply chain management on the competitive advantage of banks in Indonesia. The data has been gathered from the employees of the banks by employing a questionnaire method and analysis has been made by using PLS-SEM. The results revealed that positive along with significant association has been observed among the change in cost, market age, capacity utilization, supply chain management and competitive advantage of banks in Indonesia. These findings have provided the guidelines to the regulators that they should expand their focus on the supply chain along with cost and market that enhance the competitive advantage of the banks that ultimately improve the performance of the banks in the country.